Research on Aesthetic Education in China Under the Background of Ideological and Political Education: Theme Transmutation, Spotlight and Prospects - Wang Yan; Huang Yun (SHS Web of Conferences, 2023)
The goal is to contribute to research on aesthetic education in China Under the background of ideological and political education, display prevailing spotlights and look at the research trends forward. From 2,998 literature on aesthetic education included in the domestic core database from 1998 to 2022, this research, turning to CiteSpace, an emerging knowledge map analysis software, interpreted research spotlights and frontiers basing key nodes of the keywords. With efforts invested in studying the theme transmutation, spotlight and prospects on the topic by clustering algorithms, here have been listed challenges hampering current researches to provide reference and chart course for subsequent research and exploration.